A Comparative Study of Coagulation Profile and Haematological Parameters in Pregnancy Induced Hypertension (PIH). - Dr. Chaithra H; Dr. Ramesh S T; Dr. Riyaz Ahmad (Tropical Journal of Pathology and Microbiology, 2021)
Aim: To evaluate the changes in PIH (Pregnancy Induced Hypertension) by using haematological and coagulation parameters like platelet count, MPV, PDW, PT and APTT.Materials and methods: A total of 150 cases comprising 75 control groups and 75 cases group (pregnancy-induced hypertension) were enrolled in the study. Hematological parameters like platelet count, MPV, PDW and coagulation parameters like PT and APTT were studied in these patients. Data entry was done in an excel spreadsheet and by using SPSS (version -20).Results: The hematological parameter - Platelet count was markedly reduced in patients with preeclampsia compared to normal pregnant patients. MPV, PDW, PT and APTT were increased which is statistically significant.Conclusion: The abnormalities about hematological and coagulation parameters in preeclampsia are the prognostic markers used as an additional diagnostic criterion for preeclampsia in rural hospitals